PROGRESSIVE VARICELLA SYNDROME WITH VARICELLA GANGRENOSA IN AN IMMUNE- COMPETENT INFANT - Sonia Bhatt; Nalini Bhaskaranand; Kashyap Udupa; Meenu Joon (Our Dermatology Online, 2013)
Varicella is common and highly contagious and affects nearly all susceptible children before adolescence. Progressive varicella syndrome is a severe complication of primary Varicella Zoster Virus (VZV) infection, with visceral organ involvement, coagulopathy, severe hemorrhage, and continued vesicular lesion development. We report a rare case of progressive varicella syndrome with varicella gangrenosa in a previously well female child of ten months. She presented with history of recurrent vesiculo-bullous skin lesions involving the chest, back and extremities since two months with dry gangrene of 1st, 3rd and right great toe. VZV Polymerase Chain Reaction (PCR) of vesicle fluid was positive. Workup for immunodeficiency state was negative. She responded dramatically to intravenous acyclovir..